Semiconductor-based dynamic heterojunctions as an emerging strategy for high direct-current mechanical energy harvesting. (May 2021) - Yang, Ruizhe; Xu, Ran; Dou, Wenjie; Benner, Matthew; Zhang, Qing; Liu, Jun
Abstract: Direct-current (DC) power generation through mechanically modulated semiconductor-based heterojunctions is a newly found physical phenomenon, where mechanical-to-electric power conversion can take place in various material systems, including e.g., metal/semiconductor sliding Schottky contact, p-n junction sliding/impact contact, metal/conducting polymer compressive contact, and liquid/semiconductor moving interface. Such systems are capable of generating a continuous DC with a current density up to 10–100 A/m 2, which is 3–4 orders of magnitude higher than the pulsed alternating current (AC) density in traditional piezoelectric and triboelectric nanogenerators. Unlike the dielectric displacement current generation mechanism in traditional methods, the DC generation is associated with a multi-scale and multi-physics interaction at the dynamic interfaces with semiconductor junctions involved. The resulting electronic excitation, which is referred to the tribovoltaic effect, and the subsequent direct electron conduction are considered to play a key role in the DC power output. In an effort to provide an overview of the novel concepts and inspiration for their applications, the fundamental aspects of the dynamic interfaces, nanoscale observation of the phenomenon, and recent progress in material and device development are summarized and discussed in this review. The dynamic DC generator concept shows great promise for scaled-up as well as miniaturized self-powering applications. Moreover, the new photo/thermal-electro-mechanical coupling effects discovered in the dynamic semiconductor heterojunctions may be exploited for hybrid energy harvesting and advanced sensing. Graphical Abstract: ga1 Highlights: Fundamentals of non-equilibrium charge transfer at metal/semiconductor interfaces have been introduced. Multi-scale and multi-physics interactions at the dynamic interfaces have been discussed. Nanoscale observation of the DC generation phenomenon in different materials system have been discussed. Recent progress of materials and interfacial engineering for scaled up DC generation have been reviewed. Device design and fabrication of the DC generator toward practical application have been reviewed.